Record-keeping, management decisions and productivity of extensive reindeer herding on the Seward Peninsula, Alaska - Renecker, Lyle A.; Chetkiewicz, Cheryl-Lesley (Rangifer, 1993)
Alaska's reindeer (Rangifer tarandus) industry has been faced with the competitive need to increase productivity but cautioned to avoid range degradation as a result of high stocking rates. Consumer demand for lean, healthy, high quality meat has increased throughout the world and has surpassed production. For herders to tap these new domestic and off-shore markets, there will be the need for higher herd numbers and animal productivity, consistent slaughter protocol, and a focused marketing plan. In this paper, we illustrate how record-keeping can benefit reindeer herders in husbandry and management decisions that are necessary to increase animal productivity and, eventually, product quality and profits. These biological parameters were tested in a Lotus® spreadsheet model designed to predict herd growth and economics. Records of three reindeer herds on the Seward Peninsula have shown that calf production for adults has ranged from 35 to 98%. Sensitivity analysis predicted that in some herds, the model was sensitive to small changes in calf survival which could result in insufficient recruitment to maintain long-term harvest. Productivity may be ultimately related to management decisions that cull animals before productivity begins to decline.